Mixed metal oxides from sucrose and cornstarch templated hydrotalcite-like LDHs as catalysts for ethyl biodiesel synthesis - Coelho, Adonis [UNESP]; Perrone, Olavo Micali [UNESP]; Gomes, Eleni [UNESP]; Da-Silva, Roberto [UNESP]; Thoméo, João Claudio [UNESP]; Boscolo, Mauricio [UNESP] (Elsevier, 2017)
Sucrose and cornstarch were used as organic templates in the synthesis of hydrotalcite-like layered double hydroxides (LDHs) prepared by the coprecipitation with partial replacement of Mg by Zn, and Al by Fe. Non-template materials were taken as references. All LDHs were used as precursors of mixed metal oxides (MMOs) by calcination and applied as catalysts for ethyl biodiesel synthesis via transesterification reactions of soybean oil and ethanol. The LDHs were characterized by XRD, TG, FTIR-ATR and the respective MMOs by SEM, BET, basicity and acidity. Crystallographic data from templated LDHs showed lower crystallinity compared to the reference homologous materials, and it was observed that cornstarch decreases the average surface areas (from 173 to 94 m2g−1) and the size of the crystallites (from 147 to 92 Å). FTIR spectra indicated carbohydrates were occluded inside the crystals. While this did not influence the number of acidic sites on the MMOs, it enhances the alkaline sites. Under the catalytic conditions of this experiment, cornstarch templated MMOs reach an average ethyl biodiesel conversion of 70% whereas those prepared with sucrose 45%, and the homologous reference materials only 36%. These results demonstrated the great potential of using carbohydrates as biotemplates in the preparation of heterogeneous catalysts for transesterification reactions.
Keywords: Bioenergy; Ethyl biodiesel; Heterogeneous catalysis; Hydrotalcites; Metal mixed oxides